Factors Related to Incidence of Stunting in Children Aged 24-59 Months in Rancatungku Village, Bandung Regency - Puspa Wati Manik, Tri Arini; Liska, Cici; Bonita, Nely (Jurnal KESANS : Kesehatan dan Sains, 2025)
Stunting is a chronic nutritional problem characterized by a child's height that is lower than the standard of age which can occur in the first 1000 days of a child's life, and is one of the main indicators of children's health status in Indonesia. This study aims to analyze factors related to the incidence of stunting in children aged 24-59 months in Rancatungku Village, Bandung Regency. The research design was based on a case control approach of 1:1 ratio between the case group and the control group with a total of 206 respondents. The sampling technique in this study is accidental sampling. Data were processed and analyzed univariate, bivariate and multivariate with Chi-Square assays. This study found a meaningful relationship between body length p-value 0.019, education p-value 0.037, history of exclusive breastfeeding p-value 0.002, protein intake p-value 0.007 and history of infectious disease p-value 0.029 with stunting incidence. And the dominant variable related to stunting incidence is the history of exclusive breastfeeding. This study suggests that health workers provide education and counselling on the importance of exclusive breastfeeding and training Integrated Health Service Post cadres so that they are more skilled and can disseminate information about stunting.